The global case fatality rate of coronavirus disease 2019 by continents and national income: A meta‐analysis. Issue 6 (25th February 2022) - Abou Ghayda, Ramy; Lee, Keum Hwa; Han, Young Joo; Ryu, Seohyun; Hong, Sung Hwi; Yoon, Sojung; Jeong, Gwang Hum; Yang, Jae Won; Lee, Hyo Jeong; Lee, Jinhee; Lee, Jun Young; Effenberger, Maria; et al.
Abstract: The aim of this study is to provide a more accurate representation of COVID‐19's case fatality rate (CFR) by performing meta‐analyses by continents and income, and by comparing the result with pooled estimates. We used multiple worldwide data sources on COVID‐19 for every country reporting COVID‐19 cases. On the basis of data, we performed random and fixed meta‐analyses for CFR of COVID‐19 by continents and income according to each individual calendar date. CFR was estimated based on the different geographical regions and levels of income using three models: pooled estimates, fixed‐ and random‐model. In Asia, all three types of CFR initially remained approximately between 2.0% and 3.0%. In the case of pooled estimates and the fixed model results, CFR increased to 4.0%, by then gradually decreasing, while in the case of random‐model, CFR remained under 2.0%. Similarly, in Europe, initially, the two types of CFR peaked at 9.0% and 10.0%, respectively. The random‐model results showed an increase near 5.0%. In high‐income countries, pooled estimates and fixed‐model showed gradually increasing trends with a final pooled estimates and random‐model reached about 8.0% and 4.0%, respectively. In middle‐income, the pooled estimates and fixed‐model have gradually increased reaching up to 4.5%. in low‐income countries, CFRs remained similar between 1.5% and 3.0%. Our study emphasizes that COVID‐19 CFR is not a fixed or static value. Rather, it is a dynamic estimate that changes with time, population, socioeconomic factors, and the mitigatory efforts of individual countries. Highlights: Europe showed the highest COVID‐19 case fatality rate (CFR) until mid‐October 2020, and North America and South America follows. Asia showed the highest CFR since the first confirmed case of COVID‐19 emerged, however, it had shown a declining tendency since March 2020. CFRs in high‐income countries showed an explosive increase compared with those in low‐income countries, which can be interpreted as due to the under‐reporting of mortality cases from COVID‐19.